Pengaruh Rasio Keuangan terhadap Harga Saham PT Unilever Indonesia Tbk pada Tahun 2010-2023 - Nababan, Pangihutan Saroha; Herlina, Listri; Kusumawardani, Astrin; Nugroho, Ilham Winar (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
PT Unilever Indonesia Tbk has recently faced challenges with declining stock prices. The company's performance, as gauged by financial ratios such as CR, DER, and NPM, significantly influences stock prices, as investors tend to favor companies with strong financial ratios. This study, which aims to determine the impact of corporate responsibility, dividend payout ratio, and net profit margin on the share price of PT Unilever Indonesia Tbk from 2010 to 2023, employs a robust quantitative approach and descriptive verification techniques. The research uses secondary data from annual financial reports and a selective sampling strategy. The analysis includes the evaluation of the coefficient of determination, regression analysis, correlation analysis, hypothesis testing, and descriptive statistics, both individually and collectively. The findings suggest that the subsequent variables have a statistically significant influence on stock prices: There was no statistically significant effect for Corporate Responsibility; there was a large effect for Debt to Equity Ratio; there was a significant effect for Net Profit Margin; and there was a statistically significant effect for the sum of the effects of CR, DER, and NPM.